Effects of Mind Mapping and Pre-Questioning on Reading Comprehension - Febrijanto, Yoyok; Kristanti, Erva Elly; Wildan, Asef (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
This study was conducted to investigate the effects of mind mapping and pre-questioning on the students’ reading comprehension and on the students’ reading comprehension levels: literal comprehension, inferential comprehension, evaluation, and appreciation. This study was a quasi-experimental design, which involved 30 Diploma Nursing Student Stikes RS Baptis Kediri. Mind mapping was used for the experimental group and pre- questioning was for the control group. The instrument was 25 item reading comprehension test incorporating the four reading comprehension levels based on Barrett taxonomy. Independent Sample t-test and Manova test were used to analyze the data, which results revealed that there was no significant difference between the students who received mind mapping and those who received pre-questioning in their overall reading comprehension and in their literal comprehension, evaluation, and appreciation level. However, there was a significant difference between the students who received mind mapping and those who received pre-questioning in their inferential comprehension